PENGARUH INTELLECTUAL CAPITAL TERHADAP KINERJA PERUSAHAAN OTOMOTIF DI BURSA EFEK INDONESIA - Haniyah, Faricha Nurul (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2014)
The purpose of this research is to find out the influence of intellectual capital which is proxy by Pulic model (VAICTM) to the companyâs performance which is proxy by market to book ratio (MBR) to the automotive company. The population is automotive companies which are listed in Indonesia Stock Exchange (IDX). In this research, the sample collection technique has been determined by using purposive sampling, and based on the determined criteria the samples are 8 automotive companies which are continuously publish their financial statement during the years of 2008 â 2012. This research is using multiple linear regressions analysis. The result of research shows that: (1) The value added capital employed (VACA) variable has significant influence to the market to book ratio (MBR) yet the negative regression coefficient shows the non-unidirectional relations between VACA and MBR. (2) The value added human capital (VAHU) variable has significant influence to the market to book ratio (MBR) and it shows unidirectional relationship between VAHU and MBR. (3) Independent variable structural capital value added (STVA) partially has significant influence to the market to book ratio (MBR) and shows unidirectional relationship between STVA and MBR.Keywords: Intellectual capital, Market to book ratio, Value added capital employed, Value added human capital, Structural capital value added.